Starting the Garden with Transplants - Danielle Treadwell; Lisa Hickey; Tabitha A. Petri; James M. Stephens (EDIS)
In the spring and fall, carefully prepared trays of young vegetable plants grace garden centers everywhere, signaling the start of garden season. Many times, the varieties available in retail centers are not the best-tasting or best-adapted varieties for our area. Starting your own vegetable transplants is fun and easy. This publication provides considerations and best practices for selecting the best crops to transplant and how to prepare transplants for home and community gardens in Florida.